Suplemento al Tesoro de la lengua española castellana - Covarrubias Orozco, Sebastián de, 1539-1613.; Dopico Black, Georgina; Lezra, Jacques, 1960-; Biblioteca Nacional (Spain). (Madrid Ediciones Polifemo, 2001)
This work is a transcription of the manuscript written by S. Covarrubias, found as the Ms. 6159 of the Biblioteca Nacional de Madrid. The manuscript covers from the word Abacuq to the word Moises. The rest of the work has not been found.
Suplemento al Tesoro de la lengua española castellana -- Biografía documental -- Apéndices -- Estudios.
Includes bibliographical references (p.[cclxxxiv]-ccciv).
Keywords: Spanish language -- Dictionaries; Covarrubias Orozco, Sebastián de, -- 1539-1613.; Electronic books